Airborne measurements over the boreal forest of southern Finland during new particle formation events in 2009 and 2010 - Schobesberger, Siegfried; Väänänen, Riikka; Leino, Katri; Virkkula, Aki Olavi; Backman, John Carl Gustav; Pohja, Toivo; Siivola, Erkki; Franchin, Alessandro; Mikkilä, Jyri; Paramonov, Mikhail; Aalto, Pasi Pekka; Krejci, Radovan; et al. (Finnish Environment Institute, 2016)
Peer reviewed